CURRÍCULO INTEGRADO DO PROJOVEM URBANO: do discurso oficial às percepções dos educadores do Programa - Cantanhêde, Rosa Maria Pimentel (2011)
The Integrated Curriculum of Urban Young pro purpose observes three humans necessities: schooling, professional qualification and citizen participation. However, it s necessary to regard the teacher s perceptions that operate it. Bibliographic, documental and camp research. Analyses the Urban Young Pro Curriculum by its constitution in the official speech level as well as its pattern s compreenhension by educators of the program. Introduces a synthesis of theories about curriculum in a Tomaz Tadeu da Silva s view (2007). Discuss integrated curriculum using Santomé (1999), Lopes (1998, 202 and 2008); Bernstein (1996) conceptions as references among others. Approachs briefly the proposals of integration in the National Curriculum Pattern to Joung and Adult education and Curriculum Guideline. For Youngs and Adults. Prsents young s Inclusion Program Emphasing the Pedagogical Integrated Urban Young pro project from interviews with 14 educators and from its respective documents (BRASIL, 2005 and 2008), IPEA (2009). The educators perform in two nucleus of São Luís named x and y. Testify, with basis in deposition of educators that curriculum s proposals Program is incorporated by these teachers without they show benefit of resetting on the school space, which is not declared as a fight and conflict arena, in favor of new curriculum reading. The educators declared that the inicial and continues training, general planning and study s guide as essentials components to the curriculum establishmen, they mentioned as a fundamental activity the integrated synthesis produced by the studens. Concludes that this integrated curriculum has a credibility, being made by the majority of interviendes educators, it s capable of to promote social insertion of youngs in the measuremen that its suggest.